"A New West in Mindanao": Settler Fantasies on the U.S. Imperial Fringe. (July 2019) - Charbonneau, Oliver
Abstract: This essay analyzes white settler formations in the Southern Philippines during the early decades of the twentieth century. Occupied by the United States in the wake of the Spanish-American War, the Muslim-majority regions of Mindanao and the Sulu Archipelago became sites of colonial experimentation and reconfiguration. This led to a brief-but-concerted push by Euro-American fortune seekers to settle the "Muslim South." Supported by U.S. policy makers and colonial officials, white colonists were drawn to Mindanao-Sulu by visions of permanent settlement and limitless economic opportunity. This analysis contends that settler attempts to build a "white man's country" in the Southern Philippines were shaped by vernaculars and modes of conquest developed on the continental frontier. It interrogates the creation of transoceanic frontier spaces in Mindanao-Sulu and the practical attempts to exploit them, which drew inspiration from diverse sources in the American West and across the colonized globe. In its study of settler fortunes and failures, the essay blurs distinctions between national and imperial peripheries, and contributes to a growing scholarly interest in reassessing the importance of U.S. extraterritorial possessions in the late nineteenth and early twentieth centuries.